Efficacy and safety of mini percutaneous nephrolithotomy in obese patients - Akbulut, Fatih (Springerplus, 2016)
PURPOSE: We aimed to evaluate the effect of obesity on surgical outcomes of mini percutaneous nephrolithotomy (Mini-PNL). METHODS: Hundred and eighty two Mini-PNL procedures were performed between May 2013 and January 2015 and their results were evaluated retrospectively. Patients were classified as non-obese (BMI, 18.5–30 kg/m(2)) and obese (≥30 kg/m(2)) groups. Obese and non-obese patients were compared according to pre-operative demographic values, intra-operative surgery techniques and post-operative results. RESULTS: BMI values of 133 patients were lower than 30 kg/m(2) while 49 patient’s BMI values were higher than 30 kg/m(2). There were no significant difference between operation time, fluoroscopy time, number of access and access sites when two groups were compared. No significant difference was found in total length of hospital stay, hemoglobin drop, and complication rates. Stone-free rates were 70.7 % in the non-obese and 71.4 % in the obese group (p = 0.9). CONCLUSIONS: Mini-PNL procedure is a safe and effective treatment modality, which should be strongly considered for obese patients with appropriate sized stones.